Profil Gaya Kepemimpinan Kepala Desa Galanggang Berdasarkan Likert’s 4-Managerial System - Marsha Medina Zhabilla; Kristian Widya Wicaksono (Student Research Journal, 2026)
This study aims to analyze the implementation of the managerial system in the Government of Galanggang Village, Batujajar District, West Bandung Regency. The analysis focuses on identifying the dominant managerial system based on leadership characteristics, motivational forces, communication processes, interaction and influence processes, decision-making processes, goal-setting processes, and control processes within the village government organization. This research employs Rensis Likert's Four Systems of Management Theory. The theory classifies managerial systems into four categories: System 1 Exploitative-Authoritative, System 2 Benevolent-Authoritative, System 3 Consultative, and System 4 Participative. The analysis is conducted using the Profile of Organizational Characteristics (POC), which consists of leadership processes, motivational forces, communication processes, interaction-influence processes, decision-making processes, goal-setting processes, and control processes. This study uses a descriptive quantitative method. The research object consists of 31 village government officials selected through purposive sampling. Data were collected through questionnaires, observation, documentation, and literature review. The collected data were analyzed using descriptive statistical techniques, including Likert scale scoring, frequency distribution, and interval class calculations to determine the dominant managerial system implemented within the organization. The findings reveal that the managerial system applied in the Government of Galanggang Village tends to fall under System 3 (Consultative System). This is indicated by the high level of trust demonstrated by village leaders toward village officials, open communication practices, employee involvement in decision-making processes, and supervisory mechanisms that support organizational performance improvement. These findings suggest that the Government of Galanggang Village has successfully implemented a consultative managerial approach that supports organizational effectiveness in village governance.